Насінна продуктивність cортів лілії (Lilium L.) колекції НБС ім. М.М. Гришка НАН України - Kykot, L.M.; Tymchenko, O.D.; Len, O.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The results of study of seed productivity at free pollination without castration of flowers of Lilium × hort. of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine collection are given. It's determined, that the overwhelming majority of sorts (72,7%) are fructiferous and to form high-grade seeds, and consequently can be used as the parent forms at realization of selection works.